2022
DOI: 10.1371/journal.pone.0272921
|View full text |Cite
|
Sign up to set email alerts
|

Supplementary honey bee (Apis mellifera L.) pollination enhances fruit growth rate and fruit yield in Paeonia ostii (family: Paeoniaceae)

Abstract: Insufficient pollination leads to low and unstable production of oil tree peony. Supplementary managed honeybees (Apis mellifera L.) in agricultural ecosystems is a common practice for addressing the problem. At this study site (N 34°38′30″ and E 112°39′43″, with an altitude of 125.5 m), we set up four pollination areas (low-density bee pollination group (LDBP), high-density bee pollination group (HDBP), blank control group (CK1) and field control group (CK2)) to examine the pollination effectiveness of differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Among all the investigated tree peony cultivars, the Y of No.46 ('Zibanbai') was the highest, reaching 337.22 g, and was followed by No.39 ('Yupantuojin'), reaching 143.56 g. There were five cultivars with a Y of more than 100 g, namely, No.62 ('Changshoule'), No.33 ('Xianchizhenghui'), No.22 ('Caiyelanju'), No.36 ('Xueyuanhongxing'), and No.38 ('Ruhuasiyu'). The Y of 'Fengdan' is similar to that of previous studies [30]. The CV of the number of seeds was 61.92%, and No.46 ('Zibanbai') had the highest number of seeds among the investigated cultivars, with more than 900, followed by No.33 ('Xianchizhenghui').…”
Section: Agronomic Traits Of Different Tree Peony Cultivarssupporting
confidence: 84%
“…Among all the investigated tree peony cultivars, the Y of No.46 ('Zibanbai') was the highest, reaching 337.22 g, and was followed by No.39 ('Yupantuojin'), reaching 143.56 g. There were five cultivars with a Y of more than 100 g, namely, No.62 ('Changshoule'), No.33 ('Xianchizhenghui'), No.22 ('Caiyelanju'), No.36 ('Xueyuanhongxing'), and No.38 ('Ruhuasiyu'). The Y of 'Fengdan' is similar to that of previous studies [30]. The CV of the number of seeds was 61.92%, and No.46 ('Zibanbai') had the highest number of seeds among the investigated cultivars, with more than 900, followed by No.33 ('Xianchizhenghui').…”
Section: Agronomic Traits Of Different Tree Peony Cultivarssupporting
confidence: 84%
“…In our preliminary study, the result showed that the seed rate and the growth rate of P. ostii were significantly improved by supplementing the A. mellifera and the B. terrestris during the flowering period in the pollination net room, which conveyed that they were both considered to be the effective pollinators of oil tree peony [37,38,44,49,50]. We measured pollen deposition per visit and compared the pollen transfer efficiency of the two species of bees in this study, and the result showed that the A. mellifera was the most effective pollinator.…”
Section: Discussionmentioning
confidence: 86%
“…Chinese agroecosystems are known for their rich diversity of pollinators. Numerous studies have been conducted to explore pollinator assemblages across China targeting a variety of major crops and fruits, including apple (Wu et al, 2019), pear (Li, Sun, et al, 2022), oilseed rape (Shi et al, 2021;Shi et al, 2022;, oil tea , alfalfa (Chen et al, 2018), buckwheat (Liu et al, 2020), oil peony (He et al, 2020;Zhang, Sun, et al, 2022), and medical crops (Ren et al, 2014).…”
Section: Practitioner Pointsmentioning
confidence: 99%
“…Chinese agroecosystems are known for their rich diversity of pollinators. Numerous studies have been conducted to explore pollinator assemblages across China targeting a variety of major crops and fruits, including apple (Wu et al, 2019), pear (Li, Sun, et al, 2022), oilseed rape (Shi et al, 2021; Shi et al, 2022; Zou, Bianchi, et al, 2017), oil tea (Li, Luo, et al, 2021), alfalfa (Chen et al, 2018), buckwheat (Liu et al, 2020), oil peony (He et al, 2020; Zhang, Sun, et al, 2022), and medical crops (Ren et al, 2014). As examples of the high diversity seen in crops, Wu et al (2019) reported 76 pollinator species for apples in Beijing's Changping district, while Shi et al (2021) reported 85 pollinator species for oilseed rape in Nanchang, Jiangxi.…”
Section: Pollinator Diversity In Chinese Agroecosystemsmentioning
confidence: 99%